Olbiogaster Osten Sacken (Diptera: Anisopodidae) from Mexico, with the description of three new species - Huerta, Heron; Dzul-Manzanilla, Felipe; Navarrete-Carballo, Juan C.; Manrique-Saide, Pablo; Hancock, E. Geoffrey (Zootaxa, 2019)
Three new species of the genus Olbiogaster Osten Sacken—Olbiogaster halffteri sp. nov., Olbiogaster nuxco sp. nov. and Olbiogaster puuc sp. nov.—are described and illustrated from Mexico, based on adult males and females collected in the states of Guerrero, Puebla and Yucatan. Comments for the species known from Mexico and key are provided.